Evaluating the Mechanical Properties of Restorative Glass Ionomers Cements - Sarah Bahammam; Dan Nathanson; Yuwei Fan (Elsevier, 2022)
ABSTRACT: Objective: The aim of this research was to assess the efficiency of 4 restorative glass ionomer cements (GICs): Fuji IX (GC), ChemFil Rock (DENSPLY), Riva Self-Cure (SDI), and Ketac Nano (3M ESPE). Materials and methods: The 4 restorative glass ionomers' diametral tensile and compressive strengths were evaluated at room temperature for 24 hours and then stored in distilled water. The universal testing machine (INSTRON 5566A) was used to record the maximum load necessary to fracture specimens. Surface wear, diametral tensile strength, and compressive strength against dental ceramic were compared using analysis of variance followed by the Bonferroni method at a significance level of 0.05. Results: Ketac Nano and ChemFil Rock were found to have better diametral tensile strength than Riva Self-Cure and Fuji IX. The significant difference between ChemFil Rock and Fuji IX (P ≤ .005) and ChemFil Rock with Riva Self-Cure (P ≤ .005) was shown by post hoc analysis. Ketac Nano had better tensile strength than Riva Self-Cure and Fuji IX. Fuji IX showed the lowest material loss of the GICs as revealed by wear against VITABLOCS Mark II (VITA Zahnfabrik). Conclusions: This study indicated a significant difference in the compressive strengths of ChemFil Rock and Riva Self-Cure. ChemFil Rock had the highest tensile strength. The diameter tensile strength of all 4 materials was statistically insignificant. Finally, Fuji IX had the least amount of material loss. ChemFil Rock was proven to be more effective than Fuji IX.